Treating imbalances of vaginal microbiota: are we standing in place or going forward? - Радзинский, В. Е.; Хамошина, М. Б.; Кайгородова, Л. А.; Календжян, А. С.; Чотчаева, А. И.; Рубцова, А. Ю. (REPRODUCTIVE ENDOCRINOLOGY, 2014)
The authors describe the modern strategy of maintaining healthy vaginal microbiota as the key factor in defending the female reproductive system against infection. The article includes a classification system and criteria used to assess the composition of vaginal flora. This classification distinguishes the following categories: normal microflora composition, asymptomatic carriage of potential pathogens, dysbiosis (vaginosis), and vaginitis. The authors provide data that support a reasonable management strategy for women at risk and describe the basic principles of therapeutic approaches used to restore vaginal flora equilibrium.